Determination of Gossypol in Hamid and Bt (Seeni 1) Cottonseed Oil using Fourier Transform Infrared Spectroscopy - Samah AM Abdelrahman; Atif AA Yassin; Mohamed Elwathig Saeed Mirghani; Nabil HH Bashir (Borneo Journal of Pharmacy, 2020)
This study was conducted to determine the gossypol content in Bt cottonseed (Seeni-1) oil by using Fourier Transform Infrared (FTIR) spectroscopy with an Attenuated Total Reflectance (ATR) element. The wavelengths used were selected by spiking refined, bleached deodorized palm oil (RBDPO) to gossypol concentrations of 0-5% and noting the regions of maximal absorbance. Absorbance values of the wavelength regions 3700-2400 & 1900-750 cm−1 and a partial least squares (PLS) method were used to derive calibration models for Hamid cottonseed oil, Seeni-1 cottonseed oil, and gossypol-spiked RBDPO. The coefficients of determination (R2) for the calibration models were computed for the FTIR spectroscopy results against those found by using the wet chemical method AOCS method Ba 8–78. The R2 was 0.8916, 0.9581, and 0.9374 for Hamid cottonseed oil, Seeni-1 cottonseed oil, and gossypol-spiked RBDPO, respectively. The standard error (SE) of the calibration was 0.053, 0.078, and 0.062, respectively. The calibration models were validated using the cross-validation technique within the same set of oil samples. The results of FTIR spectroscopy as a useful technique determining gossypol content in crude cottonseed oil showed that there is a significant difference (p <0.05) in the amount of gossypol content in Hamid and Bt Seeni-1 cottonseed oils.